PENGARUH PENGEMBANGAN KARIR, GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PEGAWAI NEGERI SIPIL DINAS SOSIAL KABUPATEN KERINCI - Deshaspitri, Deshaspitri; Elfiswandi, Elfiswandi; Yulasmi, Yulasmi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
Research entitled "The Influence of Career Development, Leadership Style and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable in Civil Servants of the Kerinci Regency Social Service". The object of this study is employees of the Kerinci Regency Social Service. The type of research used in this study is quantitative causality research, the data collection method is by distributing questionnaires. The analysis technique used is multiple linear regression analysis with the help of the smartPLS program. The sampling technique in this study used saturated samples by analyzing 50 respondents. Based on the results of the analysis, it can be concluded that career development has a positive and significant effect on job satisfaction. Leadership style has a positive and significant effect on job satisfaction. Work motivation has a positive and insignificant effect on job satisfaction. Career development has a positive and significant effect on employee performance. Leadership style has a positive and significant effect on employee performance. Work motivation has a positive and insignificant effect on employee performance. Job satisfaction has a positive and insignificant effect on employee performance. Job satisfaction does not mediate the effect of career development on employee performance. Job satisfaction does not mediate the effect of leadership style on employee performance. Job satisfaction does not mediate the influence of work motivation on employee performance.